PS-004 Efficacy of a closed loop medicines administration process to reduce the probability of medicines errors. (24th February 2014) - Baehr, M; Van der Linde, A; König, R; Melzer, S; Langebrake, C
Abstract : Background: Medicines errors are common, costly, and responsible for clinically important problems. The main error-prone process steps are prescription, transcription, dispensing and administration. Different strategies to prevent medicines errors like implementation of computerised physician order entry (CPOE), pharmacy validation, unit-dose supply, and barcoding at point of care are discussed. With a combination of different strategies a closed loop of medicines administration can be achieved, which should be most efficient to prevent medicines errors. Purpose: To evaluate the efficacy of a closed loop medicines administration process as designed at University Medical Centre Hamburg Eppendorf to reduce the probability of medicines errors. Materials and methods: 3, 111 medicines for oral use were checked shortly before administration on two different wards (oncology and neurosurgery). The medicines were checked with respect to 12 quality criteria defined by Groth-Tonberge et al 1 : right order, right patient, identity, dosage form, strength, light and moisture-protection, date of expiry, correct crushing, dose, daily dose, time of administration. Results: Overall 3, 111 medicines were analysed. 2, 981 (95.6%) were unit doses delivered by the pharmacy, 130 (4.4%) were manually dispensed by nurses (PRN medicines etc.). In ward A 1, 640 medicines were checked, revealing 41 deviations (error rate 2.5%). 16 deviations referred to unit-dose medicines (error rate 1.0%) and 25 discrepancies were noted in the manual supply (error rate 48.1%). In ward B 1, 471 medicines were checked, 8 discrepancies were observed (error rate of 0.5%). 5 deviations referred to unit-dose medicines (error rate 0.4%) and 3 deviations were found with manually dispensed medicines (error rate 3.8%). Conclusions: The observed error rates were significantly lower than those recognised in a comparable study* which was done in a hospital where CPOE without unit-dose distribution was implemented. Due to the fact that a deviation does not necessarily generate a medicines error, the very low rate of deviations observed in this study shows that the probability of the occurrence of errors is significantly reduced by a closed loop medicines administration process. Reference: Groth-Tonberge C, Häckh G, Strehl E, Hug, M. Führt die elektronische Verordnung zu einer höheren Arzneimitteltherapiesicherheit? Krankenhauspharmazie 2012;33: 476-9 No conflict of interest.